Detection of PDGFRA mutations at exons 12 and 18 among chronic myeloid leukemia patients treated with imatinib mesylate - Razali, Ruzi Hamimi (2015)
Imatinib mesylate (IM) resistance is an emerging and major challenge in the treatment of patients with chronic myeloid leukaemia (CML). Resistance toward IM can be divided into BCR-ABL dependent pathways and BCR-ABL independent pathway. In this study, the BCRABL independent pathway was investigated; the involvement of PDGFRA mutation as a mechanism of resistance in Philadelphia positive CML patients treated with IM. The PDGFRA belongs to the tyrosine kinase Class III; not only contribute to haematopoiesis development but also has been implicated in cancers. Mutation of PDGFRA leads to constitutive activation causing spontaneous proliferation. PCR-DNA sequencing analyses were carried out to detect exons 12 and 18 of PDGFRA mutations. Eighty-six patients from five tertiary hospitals around peninsular Malaysia in different phases of Philadelphia-positive CML who were treated with IM from 2010 until 2013 were evaluated (IM-responsive patients, n= 43; IM-resistant patients, n=43). These samples were archived from the earlier CML project. Of all the patients in resistant group, 32 patients in chronic phase CML; 7 patients in accelerated phase CML; and 4 patients in blastic phase CML. Patients aged from 20 until 73 years were categorized into a range of age group from younger patients (age younger than 60 years) till older patients (age 60 years or older). Polymerase chain reaction amplifications were performed on the selected hotspots; exons 12 and exon 18 followed by screening for mutations by direct sequencing in 43 resistant and 43 responsive CML samples. Sequencing results were aligned by using Basic Local Alignment Search Tool (BLAST) to compare a query sequence with a reference sequences. Resistant patients predominate by female and the median age was 43. There were 74% of the resistant CML in chronic phase. None of the CML patients in this study exhibit any mutation on the hotspot exons 12 and 18 in PDGFRA. This study shows higher frequency of IM resistance notable in female and occurring mainly in younger age population. The absence of PDGFRA mutation at exons 12 and 18 may suggest that other regions of this gene could be involved. Majority of the study samples were from chronic phase patients might contribute to the negative mutation finding. Future study should be directed towards finding more potential exons by selecting more patients in advance stage in order to yield higher mutation frequency. Additional clinical and pathogenetic studies are needed to understand the association between PDGFRA and IMresistant CML.